Green Synthesis of Zinc Oxide Nanoparticles using Eucalyptus Lanceolata Leaf Litter in the Control of Bacterial and Fungal Crop Diseases - Vanarotti, Dr. Mohan B.; Jawahar, Dr.C.P. (Migration Letters, 2023)
Nanotechnology is a significant area of scientific inquiry that has garnered considerable attention from scholars in the contemporary period. Various plant materials are being explored as potential resources in green chemistry-based techniques for producing metal Nanoparticles (NPs). This is in response to the adverse impacts of synthetic chemicals, which contribute to significant abiotic climate change concerns in modern agriculture. The primary categories of crop diseases are those resulting from bacterial and fungal infestations. Once a plant becomes infected, it can pose a significant danger to the growth of crops, resulting in a decrease in yield and quality. Furthermore, such infections can adversely affect food safety, creating a health concern for humans. This work aimed to investigate the process of Green Synthesis and Characterisation of Zinc Oxide Nanoparticles (GSC-ZnO-NP) utilizing an extract derived from Eucalyptus lanceolatus (specifically, leaf litter). The paper intended to control bacterial and fungal crop diseases using the GSC-ZnO-NP in conjunction with Eucalyptus lanceolatus extracts. The sample’s crystalline structure and surface characteristics have been evaluated using X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The antimicrobial activity of the proposed GSC-ZnO-NP was evaluated against bacterial and fungal isolates from infected crops. The progressive augmentation in magnitude ranging from 10° to 30° in XRD signifies the emergence of ZnO-NPs characterized by distinct and well-defined crystalline configurations. Also, the antimicrobial efficacy of the Zn-NPs extract was comparable to or surpassed that of Fluconazole, suggesting the prospective use of this environmentally-friendly manufactured nanomaterial as a substitute or adjunct therapy for bacterial and fungal infections caused by these microorganisms in crops.